1967
DOI: 10.1002/j.2050-0416.1967.tb03088.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Strain of Barley With Starch of High Amylose Content

Abstract: A type of barley has been discovered in which the amylose content of the starch is approximately double that of all normal varieties of barley. This high amylose strain (Glacier, Scottish Plant Breeding Station number AC 38) appears to be a home‐grown variant of the Canadian 6‐row barley Glacier and the amylose content of the parent variety obtained from Canada is no higher than that of normal barley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…1, 2) and with OD ( Fig. 1) (Merritt 1967) and an experimental barley selection, , is demonstrated in Fig. 2.…”
Section: Introductionmentioning
confidence: 94%
“…1, 2) and with OD ( Fig. 1) (Merritt 1967) and an experimental barley selection, , is demonstrated in Fig. 2.…”
Section: Introductionmentioning
confidence: 94%
“…Another example is high-amylose barley, which generally contains 40-70% of amylose in the starch. The mutant Glacier Ac38 was the first reported and was shown to contain 44-47% amylose [7]. Later it was shown that the controlling gene was amo1, which is located on chromosome 5 (1H) [8].…”
Section: Introductionmentioning
confidence: 98%
“…Amylose has the property to form a thermally stable RS3 complex, resistant to amylases . It is known from literature that native barley grain starch, as used in our study, consists of around 25% amylose and 75% amylopectin . Usually, high amylose barley varieties, containing up to 45% amylose , are used in studies like this to yield high amounts of RS .…”
Section: Resultsmentioning
confidence: 99%